IMPLEMENTASI KEBIJAKAN BANTUAN PROGRAM INTERVENSI BAGI MASYARAKAT MISKIN TAHUN 2016 - Mukti Sumarsono (Universitas Kadiri, 2019)
The research in this thesis was motivated by the implementation of intervention programs for the poor where the aim of implementing this program was to improve the welfare of the poor, as well as to reduce poverty. The formulation of the problem in the writing of this thesis is (1) How is the effectiveness of the intervention program assistance carried out by the government to reduce the number of poor people. (2). What factors are supporting or inhibiting the implementation of intervention program assistance for the poor. The research method, this study uses a qualitative approach with the type of descriptive research. The dissemination activities turned out that not all villages carried out these activities for various reasons such as fear of protests from their citizens. There are also those who do unofficially when there are activities in the environment. Actually, the implementation of this socialization has already been carried out with implementation instructions which are carried out in stages from the district level and continued to the sub-district level and continued to the village level. At this time at the village level, problems often occur.